Concise review: Geminin—a tale of two tails: DNA replication and transcriptional/epigenetic regulation in stem cells - Patmanidi, Alexandra L; Champeris Tsaniras, Spyridon; Karamitros, Dimitris; Kyrousi, Christina; Lygerou, Zoi; Taraviras, Stavros (Stem Cells, 2017)
Molecular mechanisms governing maintenance, commitment, and differentiation of stem cells are largely unexploited. Molecules involved in the regulation of multiple cellular processes are of particular importance for stem cell physiology, as they integrate different signals and coordinate cellular decisions related with self-renewal and fate determination. Geminin has emerged as a critical factor in DNA replication and stem cell differentiation in different stem cell populations. Its inhibitory interaction with Cdt1, a member of the prereplicative complex, ensures the controlled timing of DNA replication and, consequently, genomic stability in actively proliferating cells. In embryonic as well as somatic stem cells, Geminin has been shown to interact with transcription factors and epigenetic regulators to drive gene expression programs and ultimately guide cell fate decisions. An ever-growing number of studies suggests that these interactions of Geminin and proteins regulating transcription are conserved among metazoans. Interactions between Geminin and proteins modifying the epigenome, such as members of the repressive Polycomb group and the SWI/SNF proteins of the permissive Trithorax, have long been established. The complexity of these interactions, however, is only just beginning to unravel, revealing key roles on maintaining stem cell self-renewal and fate specification. In this review, we summarize current knowledge and give new perspectives for the role of Geminin on transcriptional and epigenetic regulation, alongside with its regulatory activity in DNA replication and their implication in the regulation of stem and progenitor cell biology. Stem Cells 2017;35:299-310.